Significant Reduction in the Binding of a Monoclonal Antibody (LYP 18) Directed Against the IIb/IIIa Glycoprotein Complex to Platelets of Patients Having Undergone Extracorporeal Circulation - Dechavanne, M; Ffrench, M; Pages, J; Ffrench, P; Boukerche, H; Bryon, P A; McGregor, J L (Thrombosis and Haemostasis, 1987)
Extracorporeal circulation (ECC) used in open heart surgery gives rise to several hemostatic defects. This work investigates the effect of ECC on patient platelets membrane glycoproteins II b/ IIIa. A monoclonal antibody (LYP 18) directed against the IIb/ IIIa complex was used on patient platelets in binding and flow cytometry studies, before and at the end of ECC. An antithrombospondin (LYP 8) monoclonal antibody and a monoclonal antibody (LYP 7) directed against an a-granule glycoprotein of 136 kdaltons, present on the platelet surface after secretion, were used in binding studies together with electron microscopy to assess the release of α-granules.Results obtained in 7 patients show a significant reduction (p <0.02) in the number of LYP 18 monoclonal antibody binding to platelets having undergone ECC (n = 49,725 ± 16,275) compared to platelets drawn before ECC (n = 72,671 ± 13,302). Flow cytometry studies indicate a decrease (p <0.02) in the percentage of platelets bearing the LYP 18 determinant following ECC (75 ± 12% vs 66 ± 14%). Binding of monoclonal antibodies LYP 8 and LYP 7 and electron microscopy studies of patient platelets having undergone ECC do not show degranulation. These results suggest possible cleavage of the IIb/IIIa complex following ECC but no release of α-granules.
Keywords: Platelets; Monoclonal antibodies; Glycoprotein IIb/IIIa complex; Release reaction; Extracorporeal circulation